2015
DOI: 10.2174/1874372201509010021
|View full text |Cite
|
Sign up to set email alerts
|

Main Allergens Observed in Patients with Contact Dermatitis in a Brazilian Population Group

Abstract: Background: The skin contact test or patch test is considered to be a fundamental tool for investigating allergic contact dermatitis (ACD). Better knowledge on the prevalence of allergens in the environment is a good strategy for enabling a better approach towards contact dermatitis (CD) cases.Objective: The objective of the present study was to evaluate the prevalence of the main allergens of ACD in a population group in the interior of the state of São Paulo, Brazil. Methods:The results from 368 patch tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A study from Brazil also gave a similar result, namely that most of the patients were female (71.5%). 7 Also, a study at Dr. Soetomo General Academic Hospital in 2019 gave a similar figure, with 79.3% of the population being female and the rest being male. 8 Based on a study conducted by Chen in 2010, it is known that women more often suffer from skin diseases such as allergic diseases, autoimmune dermatoses, hair diseases, and pigmentary disorders.…”
Section: Discussionmentioning
confidence: 78%
“…A study from Brazil also gave a similar result, namely that most of the patients were female (71.5%). 7 Also, a study at Dr. Soetomo General Academic Hospital in 2019 gave a similar figure, with 79.3% of the population being female and the rest being male. 8 Based on a study conducted by Chen in 2010, it is known that women more often suffer from skin diseases such as allergic diseases, autoimmune dermatoses, hair diseases, and pigmentary disorders.…”
Section: Discussionmentioning
confidence: 78%
“…This study discovered that the greater predominance of patients with ACD was female. A study in a Brazilian population group 8 and North American Contact Dermatitis Group Moreover, the 15-44 age group is a productive age group. This group of people was exposed to many sources of allergen, especially from the occupational environment.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Palembang 3 reported that the 3 most frequent allergens were nickel sulphate, fragrance mix, and 4-phenylenediamine free base. Calamita et al 8 reported nickel sulphate, perfume mix, and thimerosal as the most frequent allergens. Moreover, the top 3 allergens in this study were metallic allergens.…”
Section: Discussionmentioning
confidence: 99%